Anak Hebat Jago Atur Waktu : Manajemen Waktu, Tanggung Jawab, dan Kemandirian - Ainu Lailla Syawa; Aldi Riyanto; Amanda Putriasha; Andriyani Andriyani; Arfian Arfian (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The "Great Kids, Great Time Managers" training module is designed to instill essential understanding and skills in time management, responsibility, and independence in elementary school-aged children. This study aims to examine the effectiveness of this training module in enhancing these three aspects in children. The method employed is descriptive qualitative with a case study approach, involving observation and interviews during the training implementation. The training results showed an increase in children's awareness and ability to manage time, complete tasks responsibly, and perform daily activities independently. This training contributes to the development of positive and adaptive children's character in the modern era.